Application of data content analysis (DEA) technology to evaluate performance efficiency: applied research in the General Tax Authority (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The aim of the research is to use the data content analysis technique (DEA) in evaluating the efficiency of the performance of the eight branches of the General Tax Authority, located in Baghdad, represented by Karrada, Karkh parties, Karkh Center, Dora, Bayaa, Kadhimiya, New Baghdad, Rusafa according to the determination of the inputs represented by the number of non-accountable taxpayers and according to the categories professions and commercial business, deduction, transfer of property ownership, real estate and tenders, In addition to determining the outputs according to the checklist that contains nine dimensions to assess the efficiency of the performance of the investigated branches by investing their available resources The dimensions are: integrity of the taxpayer database, effective risk management, support for voluntary compliance, submission of tax returns on time, payment of tax obligations on time, accuracy of reporting in tax returns, resolution of tax disputes, efficiency in revenue management, accountability and transparency The ready-made statistical program SPSS was adopted in calculating the weighted arithmetic mean, and the case study approach was used, and the data content analysis model was applied using the ready-made program DEAP to determine the efficiency of the researched branches for the year 2018 The research reached a set of conclusions, the most prominent of which was that the branches represented by Karrada and Karkh Center achieved high levels of performance efficiency that reflect the extent of their investment of their available resources efficiently.